Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis